The Influence of Agile Leadership on the Clean Wather Assistance Program: Mas Lindra’s Program Fluttering in Grabagan District - Nando Oktavian Pratama; Ahmad Taufiq; Heny Suhindarno (Jurnal Ilmiah Global Education, 2026)
Grabagan District in Tuban Regency is an area that often experiences drought due to the geographical conditions of highlands and limestone soils, so that access to clean water is a chronic problem for the community. The local government initiated the Mas Lindra Berkibar Program as an effort to provide clean water assistance for affected residents. However, the effectiveness of this program is greatly influenced by the ability of leadership in responding to rapidly changing field conditions. This study aims to analyze the influence of agile leadership on the success of clean water assistance programs in Garabagan District. The study method used was quantitative descriptive using a survey approach to 110 respondents, consisting of beneficiaries and parties involved in the implementation of the program. The research instrument used a likert scale questionnaire of 1-5 and the data were analyzed using SPSS Version 26 through validity, realism, classical assumption test, and t-test. The findings of the study indicated that agile leadership had a positive and significant impact on the success of the program. This indicates that leadership that is adaptive, collaborative, quick to make decisions, and responsive is able to improve the accuracy of water distribution, coordination effectiveness, and community participation. These findings confirm that the implementation of agile leadership is a strategic factor in strengthening the effectiveness and sustainability of clean water assistance programs in drought-prone areas such as grabagan.